The Effect of Art Therapy on Depression Levels in Parents of Children with Cancer - Wulanningrum, Dian Nur; Suryandari, Dewi; Putri, Diyanah Syolihan Rinjani; Saputra, Irvan Wydias (GLOBAL HEALTH SCIENCE GROUP, 2024)
Childhood cancer is a serious condition characterized by the abnormal growth of cells in children. Treatment for children with cancer, both through medical and psychological therapies, can affect mental health, including stress, anxiety, and the risk of depression in parents. Mental health issues in parents of children with cancer can impact the caregiving process. One approach to reduce the risk of depression in these parents is art therapy. Objective to determine the effect of art therapy on depression levels in parents of children with cancer. This study used a quasi-experimental approach with a one-group pretest-posttest design without a control group. The sampling technique used was accidental sampling, with total of 39 respondents. The data analysis used the Wilcoxon test. Data analysis showed a p-value of 0.000. This study indicates that art therapy has a significant effect on reducing depression levels in parents.